NEW ASPECTS OF ENDOMETRIAL HYPERPLASIA TREATMENT - Reznichenko, G.І.; Reznichenko, N.Yu.; Shishkina, О.І. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The artcle presents dataconcerning «Buserіn»nasal application efficacy in patients with endometrial hyperplasia. It was proved high clinical potency and absense of side effects.